Genetic variability and differentiation among the populations of Dice snake, Natrix tessellata (Sepentes, Colubridae) in the Iranian Plateau. (June 2017) - Rastegar-Pouyani, Eskandar; Ebrahimipour, Farnaz; Hosseinian, Saeed
Abstract: The Dice snake, Natrix tessellate, is one of the widely distributed but poorly studied reptiles of the Iranian plateau. Here, we sequenced a partial fragment of Cyt b for 14 samples of Natrix tessellata from Iran. The data were added to the previously published data from GenBank. The phylogenetic analyses indicated that the Iranian populations of N. tessellata are well divided into two major clades. The north, eastern and NE populations of Dice snake in Iran in an association with the Central Asian populations constitute the first clade which is in turn a sister clade to the European populations. The other clade that is placed in the base of the whole Dice snake clade, is formed by the southern and western Iranian populations. These are separated from the first group with high bootstrap and posterior probability values. Position of the western and southern Iranian populations in the phylogenetic tree and its close relation to the N. natrix samples, included in the analyses, imply that the group is most ancient among all populations of Dice snake in the Palearctic region with a long history in the area. Highlights: Biological Journal of Linnean Society, volume 87, issue 1, January 2006, 127–143. Organisms Diversity and Evolution, Volume 9, Issue 3, August 2009, 201–214. Handbuch der reptilien und amphibien Europas, volume 3, issue 2, July 1999, 581–644.